Effects of heat treatment on synthetic graphites for carbon nanotubes synthesis - Sanip , S. M.; Abidin, Z. R. Z.; Buang, N.; Aziz, M.; Ismail, Ahmad Fauzi (World Scientific Publishing, 2004)
Carbon materials are well known for their excellent adsorbent property towards gases. Much work has been done to improve the properties of carbon materials as to enhance their absorption capacity towards gases. Recent developments have resulted in the discovery of novel carbon materials such as carbon nanotubes. Numerous researches have shown that carbon nanotubes have excellent capacity for hydrogen storage. However, significant research has been undertaken to further improve the adsorption capacity through the advancement in synthesis methods for the fabrication of carbon nanotubes. Among the starting material widely employed for synthesis of carbon nanotubes is high purity graphite. Therefore, purpose of this work is to investigate the effect of thermal treatment on several synthetic graphites. Thermal treatment was conducted at temperatures ranging from 400â€“800Â°C at different dwelling times. The morphology and surface analysis of the graphites were examined using Scanning Electron Microscope and nitrogen gas adsorption techniques, respectively. It was found that temperature, time and conditions of treatment significantly change the surface structure of the graphites. A decrease in particle size was observed due to the release of internal surface area